Hubungan Beban Kerja Dengan Tingkat Stres Perawat Yang Bekerja Sebagai Perawat Lansia Di Jepang (Studi Kasus Alumni Stikes Buleleng) - Putu Cicilia Septipani; Anak Agung Ratih Wijayanti (STIKES Ngesti Waluyo, 2025)
Workload is one of the factors often associated with stress levels among healthcare professionals, particularly nurses working abroad under demanding conditions. However, limited research has explored the relationship between workload and stress among Indonesian nurses employed as elderly caregivers in Japan. This study aimed to analyze the relationship between workload and stress levels among Indonesian nurses, specifically alumni of STIKes Buleleng working in Japan. The research employed a quantitative approach with a cross-sectional design. The sample consisted of 21 respondents selected using a Total sampling. The instruments used were a workload questionnaire and the Perceived Stress Scale (PSS) to measure work-related stress. Data were analyzed using Spearman’s correlation test with a significance level of 0.05. The results showed a p-value of 0.566 (p > 0.05) with a correlation coefficient of 0.133, indicating no significant relationship between workload and stress levels among nurses. Thus, the null hypothesis (H0) was accepted and the alternative hypothesis (H1) was rejected. These findings suggest that other factors beyond workload, such as social support, cultural adaptation, and coping mechanisms, may play a more substantial role in influencing stress levels among Indonesian nurses working in Japan.